A new species of Ischnocnema Reinhardt and Lütken, 1862 (Anura: Brachycephalidae) of the I. lactea species series from southeastern Brazil - Taucce, Pedro P. G.; Zaidan, Bárbara F.; Zaher, Hussam; Garcia, Paulo C. A. (Zootaxa, 2019)
We describe a new species of Ischnocnema from the Serra da Bocaina mountain range, state of São Paulo, southeastern Brazil, based on morphological, bioacoustic, and mtDNA data. The new species is retrieved with high support values within the I. lactea species series as the sister species of I. spanios. Ischnocnema bocaina sp. nov. is characterized by its medium size (18.6–19.0 mm), a smooth venter, a rounded snout in dorsal view and acuminate in lateral view, a slightly expanded subgular, single vocal sac, a round and whitish, poorly-developed glandular-appearing nuptial pad on the dorsal surface of the thumb, and a nonpulsed advertisement call with 9 to 18 notes. We raise to 38 the number of Ischnocnema species, the 12th described in the past 10 years.